Development of semisolid pharmaceutical forms with mometasone furoate - Rédai Emőke Margit; Jakab Boglárka; Vlad Robert Alexandru; Antonoaea Paula; Todoran Nicoleta; Sipos Emese; Ciurba Adriana (Acta Marisiensis - Seria Medica, 2023)
This study aims to develop semisolid pharmaceutical forms for the topical administration of mometasone furoate.